SISTEM PAKAR DIAGNOSIS CORONA VIRUS “ViroCHECK” MENGGUNAKAN ALGORITMA DECISION TREE - Lubis, Hendarman -; Temartenan, Jecklyn Shindy; Faizah, Safira (STMIK BINA PATRIA, 2025)
The rapid spread of the virus, with symptoms ranging from mild to severe, makes early diagnosis and detection crucial in preventing and controlling the spread of this disease. Limited laboratory testing capacity, especially in areas with minimal healthcare facilities, requires a system capable of facilitating early identification based on symptoms and patient history, quickly, accurately, and efficiently. One approach is an expert system. The